2016
DOI: 10.1089/dna.2015.2819
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oligoadenylate Synthetase Gene Cluster and DC-SIGN (CD209) Gene Polymorphisms with Clinical Symptoms in Chikungunya Virus Infection

Abstract: Biology and pathogenesis of chikungunya virus (CHIKV) are not clearly established. Host factors play an important role in determining the progression and severity of the disease. Polymorphisms in the promoter region of CD209 gene (rs735239, rs4804803, rs2287886) and OAS1 (rs1131454 and rs10774671), OAS2 (rs15895 and rs1732778), and OAS3 (rs2285932 and rs2072136) genes were investigated in 100 patients with CHIKV infection and 101 healthy controls to find out the association of these polymorphisms with CHIKV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…In an Indian population of 100 chikungunya patients and 101 controls, Chaaithanya et al examined the polymorphisms in CD209 and OAS genes and concluded that both OAS and CD209 gene polymorphisms influence the risk of developing clinical symptoms in patients with chikungunya. The same group further screened for the presence of CATT microsatellite repeat at −794 promoter position and the presence of a mutation at −173* in the MIF gene in four patients with acute flaccid paralysis (AFP), three patients with chronic arthropathy (CAR) after chikungunya fever and in seven healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In an Indian population of 100 chikungunya patients and 101 controls, Chaaithanya et al examined the polymorphisms in CD209 and OAS genes and concluded that both OAS and CD209 gene polymorphisms influence the risk of developing clinical symptoms in patients with chikungunya. The same group further screened for the presence of CATT microsatellite repeat at −794 promoter position and the presence of a mutation at −173* in the MIF gene in four patients with acute flaccid paralysis (AFP), three patients with chronic arthropathy (CAR) after chikungunya fever and in seven healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, rs4804803 affected a Sp1 binding site and the level of transcription of DC-SIGN, with lower DC-SIGN expression for G allele in rs4804803 [30]. The population-based genetic association studies indicated that the polymorphism of rs4804803 was related to the susceptibility of HIV-1, tuberculosis, Chikungunya [38,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dendritic cell-specific intercellular adhesion molecule 3-grabbing nonintegrin (DC-SIGN) is an essential factor for enhancing the infectivity of alphaviruses such as CHIKV and Semliki Forest virus [97]. Additionally, DC-SIGN or CD209 gene polymorphisms appear to be associated with the clinical progression of chikungunya fever [98]. Furthermore, previous study have identified the interaction host protein partner of CHIKV E2 protein using a yeast two-hybrid assay with human brain cDNA library.…”
Section: Cellular Entry Factors For Chikv Infectionmentioning
confidence: 99%